Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jgm.3436
|View full text |Cite
|
Sign up to set email alerts
|

The role of ABCB1 gene polymorphisms in steroid‐resistant nephrotic syndrome: Evidence from a meta‐analysis of steroid‐receiving patients

Abstract: Previous studies in nephrotic syndrome have shown that three common variants in the ABCB1 gene, including rs1128503, rs2032582, and rs1045642, change the expression and activity of ABCB1, which may be responsible for the drug resistance. However, as a result of the inconclusive outcomes of these studies, we performed a meta‐analysis to validate the association between ABCB1 polymorphisms and the susceptibility of steroid‐resistant nephrotic syndrome (SRNS). The association was evaluated by calculating the odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
(193 reference statements)
0
8
1
Order By: Relevance
“…MG is a multifactorial disease involving complex genegene and gene-environment interactions (34)(35)(36). No genegene interactions were identified among possible SNP combinations in GMDR analysis, but we cannot exclude the possibility of other multiple interactions that influence the therapeutic effects of MG. Several investigations suggested that MDR1, NR3C1, and FKBP5 polymorphisms may confer resistance to immunosuppressive therapy (37)(38)(39). The present study did not find any association between their genotypes and refractory MG. Further work targeting more diverse genotypes will be necessary.…”
Section: Discussioncontrasting
confidence: 74%
“…MG is a multifactorial disease involving complex genegene and gene-environment interactions (34)(35)(36). No genegene interactions were identified among possible SNP combinations in GMDR analysis, but we cannot exclude the possibility of other multiple interactions that influence the therapeutic effects of MG. Several investigations suggested that MDR1, NR3C1, and FKBP5 polymorphisms may confer resistance to immunosuppressive therapy (37)(38)(39). The present study did not find any association between their genotypes and refractory MG. Further work targeting more diverse genotypes will be necessary.…”
Section: Discussioncontrasting
confidence: 74%
“…Resistance of the cancer cell to chemotherapy exaggerates the problem of increased cancer-associated mortality and morbidity [ 1 ]. The increased expression and activity of P-gp diminishes drug delivery to cellular targets and increases the MDR of cancers [ 2 , 4 , 5 ]. Indeed, clinical evidence implicates P-gp with therapy failure and poor prognosis [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efflux of xenobiotics is a powerful mechanism leading to MDR during cancer chemotherapy [ 2 , 3 ]. Unfortunately, like many anticancer agents, doxorubicin suffers extrusion through the cell membrane by the action of P-gp [ 12 , 25 , 26 ], dramatically diminishing its efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations